2017
DOI: 10.1038/s41598-017-10789-x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed invasive ductal and lobular carcinoma has distinct clinical features and predicts worse prognosis when stratified by estrogen receptor status

Abstract: In order to investigate clinicopathological characteristics and prognosis of mixed invasive ductal and lobular carcinoma (IDC-L), 209,109 primary breast cancer patients diagnosed with invasive ductal carcinoma (IDC), invasive lobular carcinoma (ILC) or IDC-L were included. It was found that IDC-L patients had lower tumor grade and higher hormone receptor positive proportions than IDC patients. Moreover, IDC-L patients were younger and had a similar hormone receptor status compared with ILC patients. Kaplan-Mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In this study, the overall results suggested similar survival outcomes between patients with ILC and IDC-L, but when stratifying by menopausal status, we noticed superior survival outcomes for patients with IDC-L. These observations were corroborated by a large analysis of the Surveillance, Epidemiology, and End Results (SEER) database, including a total of 209,109 patients [22]. In the SEER analysis, Xiao et al compared survival outcomes based on histology, including 172,379 patients with IDC, 17,503 patients with ILC, and 19,227 patients with IDC-L.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, the overall results suggested similar survival outcomes between patients with ILC and IDC-L, but when stratifying by menopausal status, we noticed superior survival outcomes for patients with IDC-L. These observations were corroborated by a large analysis of the Surveillance, Epidemiology, and End Results (SEER) database, including a total of 209,109 patients [22]. In the SEER analysis, Xiao et al compared survival outcomes based on histology, including 172,379 patients with IDC, 17,503 patients with ILC, and 19,227 patients with IDC-L.…”
Section: Discussionsupporting
confidence: 78%
“…By contrast, the HR for the comparison of IDC‐L versus ILC decreased over time, indicating better long‐term prognosis for IDC‐L versus ILC. When evaluating the differences in outcomes between IDC‐L and ILC, patients aged >50 years diagnosed with IDC‐L had superior outcomes . Although the larger sample size from the SEER analysis provided robust prognostic information, the lack of detailed clinicopathologic information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that patients with IDC had better disease-free survival and marginally better BCSS relative to those with IDLC [11]. In addition, IDLC may predict poorer prognosis than IDC in both ER(+) and ER(−) subgroup [15], in which the status of HER2 was absent. We found that IDLC showed better OS but not BCSS compared with IDC in the multivariate model, which was consistent with the results of survival curves after matching.…”
Section: Discussionmentioning
confidence: 96%
“…2 ILC tends to be more bilateral, multifocal, larger tumors, high ER and PR expression and lower HER expression compared to IDC. 6 There has been an intermediate classification with both of these types referred to as IDC-L. WHO categorizes it as "having an ILC pattern in at least 50% of the tumor and an IDC pattern in between 10% and 49%". 6 Breast Cancer specific survival curve indicates that those with IDC-L fare better than the IDC or ILC group.…”
Section: Introductionmentioning
confidence: 99%